PENGOLAHAN LIMBAH BAGLOG MENJADI PUPUK KOMPOS DI DESA JAGO, KEC. PRAYA, KAB. LOMBOK TENGAH - Ghaisan, Tsalis Adli; Oktobian, Marsila Vio; Mutohharoh, Azwajum; Saputra, I Nyoman Aditya Angga; Baasyir, Adin Purna; Nurmalasari, Baiq Dewi; Amini, Ertina; Apriana, Mala; Kinaya, Khalifa; Sani, Fathul (Universitas Mataram, 2024)
This article discusses the potential of baglog waste management into compost in the village of Jago, located in Praya Subdistrict, Central Lombok Regency. The study was conducted using survey and interview methods to evaluate the agricultural practices, environmental impact, and sustainability efforts in the region. The findings reveal that the conversion of baglog waste—byproducts of mushroom cultivation—into compost offers a promising solution for enhancing soil fertility while reducing environmental pollution. This practice not only supports sustainable agriculture but also provides an eco-friendly alternative to chemical fertilizers. With the right approach, the management of baglog waste into compost can significantly contribute to the sustainable development of the village, ensuring that agricultural productivity and environmental health are maintained for future generations.